1997
DOI: 10.1212/wnl.48.6.1533
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of short‐duration timing associated with damage to the suprachiasmatic region of the hypothalamus

Abstract: The neural bases of circadian rhythmicity have been demonstrated in a variety of animal species, including primates. Yet, the brain mechanisms underlying time experience and the timing of behaviors of shorter duration are still not well understood. In the present study, we demonstrate disruption of short-duration timing capacity in AH, a patient with damage to the suprachiasmatic (SCN) region of the hypothalamus. AH exhibited extreme inconsistency in her rate of tapping production on a motor continuation parad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Severely deficient temporal processing in the psychological present has previously been reported in spontaneously confabulating and disorientated amnestic patients [28], whose deficit reflects a confusion of memory traces from temporally distinct events [29,32,33], and in a patient with a hypothalamic lesion associated with a severely disrupted circardian rhythm [6]. Deficient processing of longer intervals has previously been reported in severely amnestic patients [19,26,40].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Severely deficient temporal processing in the psychological present has previously been reported in spontaneously confabulating and disorientated amnestic patients [28], whose deficit reflects a confusion of memory traces from temporally distinct events [29,32,33], and in a patient with a hypothalamic lesion associated with a severely disrupted circardian rhythm [6]. Deficient processing of longer intervals has previously been reported in severely amnestic patients [19,26,40].…”
Section: Discussionmentioning
confidence: 78%
“…Given the anatomical basis of spontaneous confabulations and disorientation, i. e. damage or disconnection of the orbitofrontal cortex [29,32], processing of the psychological present probably depends on an intact orbitofrontal area and intact limbic input from the amygdala and the dorsomedial nucleus [31]. A similar deficit was recently demonstrated in a patient with a hypothalamic tumour who failed to continue to tap at a rhythm of approximately 2 Hz and to discriminate between serially presented intervals around 400 ms [6]; structures having projections with the above limbic structures may thus be involved in temporal processing within the psychological present.…”
Section: Introductionmentioning
confidence: 88%
“…This shared regression of precision measures implies a similarity between short interval and circadian timing mechanisms, which are in keeping with work suggesting that there may be interplay between these systems. These include a clinical study describing a human with an suprachiasmatic nucleus (SCN) lesion who showed abnormal variability in tapping continuation of 550 ms intervals and impaired duration discrimination of 400 ms, while tone intensity discrimination was unaffected (Cohen et al 1997). Furthermore, the drug phospho fluoridate perturbs both circadian rhythm and duration comparisons (Raslear et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Direct evidence for the functionality of the SCN-DMH-LC circuit comes from patients with a lesioned SCN who fail to modulate attention, dysregulating the timing of the attention focus (Cohen et al, 1997). Also with respect to hyperactivity, Sylvester et al (2002) described a modulating role of SCN as suggested in studies with rats (Stephan and Zucker, 1972).…”
Section: Dysfunction In Adhdmentioning
confidence: 99%